Many geraniums dead, one computer scientist down - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
He started his career as a computer scientist at IBM in Montpellier, France. When David Rajaonson returned home to Madagascar, an unexpected niche opened up for him, in the form of low production of geraniums in neighbouring Réunion. How about...